Effect Adding PVA Polymer on Structural and Optical Properties of TiO2 Thin Films - Saleh, Arwa Fadil; Jaffar, Ahmed Mousa; Samoom, Najim A; Mahmmod, Marwa Wailed (Al-Nahrain Journal of Science, 2018)
Thin films of titanium dioxide TiO2 pure and TiO2:PVA polymer were prepared using chemical spray pyrolysis technique on glass substrate preheated at (350 oC) for TiO2 pure, and at (160 oC) for TiO2:PVA. with spray rate 3sec./1min, and thickness (250nm). The investigation of (XRD) indicates that structural of TiO2 pure and TiO2: PVA thin films they are polycrystalline and XRD investigation is anatase titanium dioxide, intensity of >101< is more than the intensity of , 105< for TiO2 and TiO2:PVA thin films. The optical properties measurement explain the effect of adding PVA on Transmittance, absorptance, refractive index, absorption coefficient and electronic transitions of prepared thin films. and their results observed that filling of PVA caused increase in optical properties generally.